Análise das propriedades do concreto permeável para diferentes consistências: agregados na faixa de 4,8 a 6,3 mm - Hisatomi, Júlia Nantes (2023)
Seeking to mitigate the environmental problems caused by impermeable areas, the application of permeable concrete to aid urban drainage has been growing, since it increases infiltration and reduces the runoff of rainwater. Permeable concrete is composed of Portland cement, coarse aggregate and water, and may contain additives, but the amount of fine aggregate is reduced or non-existent. Its benefits include reducing the pH and pollutants that may be present in the water, reducing noise pollution and the heat island effect. This work seeks to analyze the physical, mechanical and hydraulic properties of permeable concrete for 5 mixes with different w/c ratios (water/cement) and P/Ag ratio (paste/aggregate) for aggregates in the range of 4.8 – 6.3 mm. Therefore, tests were carried out for density in the fresh and hardened state, ultrasound, constant head permeameter and compressive strength. The results showed that the increase in the w/c and P/Ag ratio resulted in an increase in density and strength, up to 17 MPa, but reduced the porosity. The hydraulic behavior can be analyzed relating porosity and the /√ parameter, since the flow regime is considered non-linear, or non-Darcian. In addition, the point used on the dosage curve directs the molding of permeable concrete satisfactorily, as the results obtained correspond to the predicted properties.